Fabrication of Large-Aspect-Ratio Micro Tool Electrodes by Bipolar Pulsed Vertical Liquid Membrane Method - Xiujuan Wu; Li Wang; Weijing Kong; Tao Yang; Yusen Hang; Yongbin Zeng (Micromachines, 2025)
To achieve efficient preparation of microfine tool electrodes with a large aspect ratio, a bipolar pulse vertical liquid membrane electrochemical etching technique was proposed. The difference in current density distribution on the surface of tungsten rods under single-ended and double-ended vertical liquid membrane methods was analyzed using COMSOL software. The effects of negative voltage and pulse width on the distribution of electrolytic products and electrode preparation were investigated. It was found that when a large number of hydrogen bubbles were generated on the surface of the electrode, the electrode lost the protection of the diffusion layer, and the length was drastically shortened. When the pulse width was large, the electrode surface was covered with a coating layer of insoluble electrolysis product, and the shortening of electrode length was suppressed. Subsequently, the effects of forward voltage and bias on electrode preparation were investigated for large pulse widths. The optimal parameters are as follows: electrolyte concentration of 0.5 M, forward voltage of 4 V, negative voltage of −2 V, pulse period of 50 microseconds, and pulse width of 40 microseconds. Finally, the tool electrode with an average diameter of about 23.8 μm and an aspect ratio of 91.2 was prepared.